Between Ideological Nostalgia and Utopia: History Proves That Paradise Lost Was Never Like That - RAMABAJA, Sadri (Journal of Posthumanism, 2025)
The period between the two world wars brought the dissolution of the empires – Austria-Hungary and the Ottoman. The creation of nation-states followed, along with economic and political transformations, along with the deepening of the ideological course, which would bring Bolshevik communism to Russia, and fascism to Europe. The collapse of Yugoslavia can be considered a warning for a new world order. Meanwhile, the collapse of the USSR and the end of the Cold War had put an end to the utopia of real socialism of the Russian model. See for this the fall of Yugoslavia was not simply a local event. It foreshadowed the transition of society to a new order, where wars, ethnic cleansing, and tensions between states and ethnic groups would continue to be an important part of global politics. This essay addresses precisely these challenges that continue to accompany the former Yugoslavia three decades after its collapse.